Conjugation of Bioactive Molecules to a Fluorescent Dithiomaleimide by Photoinduced and BEt3‐Initiated Thio‐Click Reactions. Issue 35 (22nd October 2015) - Lázár, László; Nagy, Miklós; Borbás, Anikó; Herczegh, Pál; Zsuga, Miklós; Kéki, Sándor
Abstract: Two versions of the free‐radical thiol–ene addition, a photoinduced reaction in the presence of 2, 2‐dimethoxy‐2‐phenylacetophenone, and a UV‐light‐free hydrothiolation using triethylborane as the initiator, were studied for the conjugation of fluorescent dithiomaleimide to biologically active compounds. A dithiomaleimide derivative bearing a vinyl ether functionality was prepared as the alkene partner. This was coupled with a range of thiols, including thiosugars, captopril, N ‐acetyl‐L ‐cysteine, and sodium 2‐sulfonatoethanethiol. The Et3 B‐initiated method was superior to the photoinduced reaction, as it minimized decomposition of the sensitive maleimide group. The vinyl ether derivative and the addition products showed green light emission in tetrahydrofuran. The compounds all showed almost identical absorption and emission spectra, proving that the structure of the thiols has no influence on the fluorescence properties of the maleimide part of the molecules. The hydrothiolation products showed relatively high quantum yields. Abstract : Thio‐click chemistry and maleimide chemistry were combined, for the first time, to couple fluorescent dithiomaleimide to biologically active compounds. Of the two activation methods tested, Et3 B‐initiated hydrothiolation was superior to photoinduced variants. All of the hydrothiolation products showed green fluorescence with relatively high quantum yields.